Lessons from ECLIPSE: a review of COPD biomarkers. Issue 7 (5th December 2013) - Faner, Rosa; Tal-Singer, Ruth; Riley, John H; Celli, Bartolomé; Vestbo, Jørgen; MacNee, William; Bakke, Per; Calverley, Peter M A; Coxson, Harvey; Crim, Courtney; Edwards, Lisa D; Locantore, Nick; et al.
Abstract : The Evaluation of COPD Longitudinally to Identify Predictive Surrogate End-points (ECLIPSE) study was a large 3-year observational controlled multicentre international study aimed at defining clinically relevant subtypes of chronic obstructive pulmonary disease (COPD) and identifying novel biomarkers and genetic factors. So far, the ECLIPSE study has produced more than 50 original publications and 75 communications to international meetings, many of which have significantly influenced our understanding of COPD. However, because there is not one paper reporting the biomarker results of the ECLIPSE study that may serve as a reference for practising clinicians, researchers and healthcare providers from academia, industry and government agencies interested in COPD, we decided to write a review summarising the main biomarker findings in ECLIPSE.